21st International Conference on Offshore Mechanics and Arctic Engineering, Volume 1 2002
DOI: 10.1115/omae2002-28056
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Mooring Analysis and Large Scale Model Tests on a Deepwater Calm Buoy in Mild Wave Conditions

Abstract: This paper describes a series of model tests aimed at gaining insight in the tension variations in the export risers and mooring lines of a CALM buoy. The test result were therefore not only analysed carefully, but were also used as input and to validate a numerical tool that computes the coupled motions of the buoy and its mooring system. The tests were carried out at a model scale of 1 to 20. Captive tests in regular and irregular waves were carried out to investigate non-linearities in the wave forces on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…CFD could be the solution for the lack of viscous damping and the absence of rotational accelerations in the fluid. Bunnik et al [25] suggested using Computational Fluid Dynamics (CFD) in the future to predict viscous forces. Palm et al [26] and Yu and Li [27] started investigating CFD for wave energy devices.…”
Section: Discussionmentioning
confidence: 99%
“…CFD could be the solution for the lack of viscous damping and the absence of rotational accelerations in the fluid. Bunnik et al [25] suggested using Computational Fluid Dynamics (CFD) in the future to predict viscous forces. Palm et al [26] and Yu and Li [27] started investigating CFD for wave energy devices.…”
Section: Discussionmentioning
confidence: 99%
“…tonnes/m 3 A = added mass matrix tonnes, tonnes.m 2 a n = normal added mass tonnes a t = tangential added mass tonnes b (1) = linear damping coefficient kNs/m, kNms/rad b (2) = quadratic damping coefficient kNs 2 /m 2 , kNms 2 /rad 2 B = potential damping matrix kNs/m, kNms/rad C = hydrostatic spring matrix kN/m, kNm/rad C Dn = normal drag coefficient -…”
Section: Nomenclature ρ = Density Of Watermentioning
confidence: 99%
“…Based on the specified full length mooring system and export risers, a truncated mooring system was designed for use in the model tests. The design of the truncated mooring system has already been discussed in Reference [2]. It was designed such, that the load-displacement characteristics of the full length mooring system were represented as accurately as possible by the truncated mooring system.…”
Section: Photographs Of the Buoy Model Are Shown In Figures 1 Andmentioning
confidence: 99%
See 2 more Smart Citations